The Historical Background of Critical Pedagogy - Aybar, Özkan; Bingöl, Zeynep Kantarcı (My University, 2023)
This article aims to reveal the historical foundations of critical pedagogy. The advocacy of the critically oriented educational philosophy known as critical pedagogy is made by philosophers and thinkers working on education such as Antonio Gramsci, Henri Giroux, Ivan Illich and Paulo Freire, who were influenced by Marxism and critical theory. The main source of critical pedagogy is the critical theory that criticizes the enlightenment and positivism put forward by the philosophers of the Frankfurt School. The main interest of critical theory is the political, social and economic movements and struggles of its age, critical theory did not directly address education. However, since the problems and determinations they have put forward are also related to education, this situation has caused them to cross paths with critical pedagogy. Critical pedagogy, which specifically points to the political dimension of education, has drawn attention to the relationship between knowledge and power, its reflection on education in general and school in particular, and its repercussions in society. Therefore, critical pedagogy finds its roots in critical theory and is inspired by it.